Persuasive Promotions: Leveraging Location Proximity in College Selection Strategies for Prospective Students - Fanani, Achmad; Syafrudin, Tomy (Indonesian Journal of Advanced Research, 2024)
This study explores the critical role of location proximity in the decision-making process of prospective students when selecting higher education institutions. Drawing upon Aristotle's persuasive theories, the research aims to craft effective promotional content that leverages the significance of location proximity in attracting students to colleges and universities. Through a mixed-methods approach, including quantitative surveys and qualitative interviews, the study investigates the extent to which location proximity influences students' decisions and develops persuasive messages based on ethos, pathos, and logos theories. Findings indicate that proximity to home significantly influences students' choices, driven by factors such as convenience, accessibility, and cost-effectiveness. By recognizing and addressing the importance of location proximity, educational institutions can enhance their recruitment strategies, bolster competitiveness, and contribute to student success. This research underscores the need for institutions to tailor offerings and promotional strategies to resonate with prospective students effectively, emphasizing the benefits of attending a nearby institution.